2011
DOI: 10.1186/1756-9966-30-88
|View full text |Cite
|
Sign up to set email alerts
|

The expression and role of protein kinase C (PKC) epsilon in clear cell renal cell carcinoma

Abstract: Protein kinase C epsilon (PKCε), an oncogene overexpressed in several human cancers, is involved in cell proliferation, migration, invasion, and survival. However, its roles in clear cell renal cell carcinoma (RCC) are unclear. This study aimed to investigate the functions of PKCε in RCC, especially in clear cell RCC, to determine the possibility of using it as a therapeutic target. By immunohistochemistry, we found that the expression of PKCε was up-regulated in RCCs and was associated with tumor Fuhrman grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
1
15
3
Order By: Relevance
“…PRKCε was also found to be more abundant in some highly metastatic OS cells at the protein level, and in some MD-OS tumors at the transcript level. Although PRKCε is known to support migration of other cell types [89,96,98,117,118], there was no evidence to support a role for PRKCε in the migration of M132 osteosarcoma cells in this study. This may indicate that the aberrant expression of PRKCε and its network in vitro and in vivo is related to a bystander effect, or that the functional relevance of this aberrant expression has not yet been elucidated.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…PRKCε was also found to be more abundant in some highly metastatic OS cells at the protein level, and in some MD-OS tumors at the transcript level. Although PRKCε is known to support migration of other cell types [89,96,98,117,118], there was no evidence to support a role for PRKCε in the migration of M132 osteosarcoma cells in this study. This may indicate that the aberrant expression of PRKCε and its network in vitro and in vivo is related to a bystander effect, or that the functional relevance of this aberrant expression has not yet been elucidated.…”
Section: Discussioncontrasting
confidence: 74%
“…Literature searches of the genes contained in the highly significant network results showed that PRKCε has been characterized in progression of prostate [82,83,84,85,86,87], breast [88,89], and renal cancers [90], as well as tumorigenesis of squamous cell carcinoma (non-melanoma skin [91,92,93,94,95], and head and neck [96,97,98,99]), as well as non-small cell lung cancer [100,101,102,103]. Additionally high expression of GNB2 is associated with an aggressive form of pulmonary adenocarcinoma (mixed adenocarcinoma with bronchioalveolar features), and shorter overall survival for patients with these tumors [104].…”
Section: Resultsmentioning
confidence: 99%
“…All the three agents resulted to be active in inhibiting cell proliferation, with a major effect observed after everolimus treatment (Figure 2A). In fact, even if both TKIs sunitinib and sorafenib were moderately effective in inhibiting proliferation of RCC cells in vitro at doses comparable to those used in our study (Juengel et al , 2009; Liu et al , 2009; Takeuchi et al , 2010; Huang et al , 2011; Kim et al , 2012), the target of everolimus, mTOR, is directly implicated in tumour cell proliferation and survival via PI3K, Akt and MAPK. The doses of drugs chosen by us and in similar studies are expected to be in the therapeutic range achieved in human studies.…”
Section: Discussionmentioning
confidence: 45%
“…Enhanced PKCε levels are associated with invasion and/or metastasis of human breast, glioma and renal cell carcinoma [7, 166, 181]. PKCε contains an actin-binding motif that positions this kinase within a cytoskeletal matrix where many PKC substrates are localized [182185].…”
Section: Pkcε: An Oncogenic and Metastatic Kinasementioning
confidence: 99%